Continuous and Daily Oral Immunotherapy for Peanut Allergy: Results from a 2-Year Open-Label Follow-On Study - Brian P. Vickery; Andrea Vereda; Caroline Nilsson; George Du Toit; Wayne G. Shreffler; A. Wesley Burks; Stacie M. Jones; Montserrat Fernández‐Rivas; Katharina Blümchen; Jonathan O’B Hourihane; Kirsten Beyer; Aikaterini Anagnostou; et al. (2020)
The randomized, controlled PALISADE trial demonstrated the benefit of daily oral immunotherapy with Peanut (Arachis Hypogaea) allergen powder-dnfp (PTAH, formerly AR101) in peanut-allergic children and adolescents.ARC004, the open-label follow-on study to PALISADE, used 5 dosing cohorts to explore PTAH treatment beyond 1 year and alternative dosing regimens in peanut-allergic individuals.Active arm (PTAH-continuing) PALISADE participants who tolerated 300-mg peanut protein at the exit double-blind placebo-controlled food challenge and placebo arm (PTAH-naive) participants could enter ARC004. PTAH-continuing participants were assigned to receive daily (cohorts 1 and 3A) or non-daily (cohorts 2, 3B, and 3C) dosing regimens; PTAH-naive participants were built up to 300 mg/d PTAH, followed by maintenance dosing. At study completion, participants underwent an exit double-blind placebo-controlled food challenge with doses up to 2000 mg peanut protein. Data were assessed using descriptive statistics.Overall, 358 (87.5%) eligible participants (4-17 years) entered ARC004 (PTAH-continuing, n = 256; PTAH-naive, n = 102). Among PTAH-continuing participants, exposure-adjusted adverse event rates were 12.94 to 17.54/participant-year and 25.95 to 42.49/participant-year in daily and non-daily dosing cohorts, respectively; most participants (83%) experienced mild or moderate adverse events. Daily dosing cohorts appeared to have higher desensitization rates than non-daily dosing cohorts. Of all PTAH-continuing cohorts, cohort 3A had the longest daily dosing duration and the highest desensitization rates. Changes in immune markers with PTAH continuation demonstrated ongoing immunomodulation. Outcomes in PTAH-naive participants mirrored those of the PALISADE active arm.Continued daily PTAH treatment beyond 1 year showed sustained safety and efficacy. Ongoing immunomodulation was observed during the second year of treatment.